THE EFFECT OF USING FLASH CARD MEDIA ON THE READING ABILITY OF SECONGRADE STUDENTS AT SD MUHAMMADIYAH 13 MEDAN, ACADEMIC YEAR 2024/2025 - Widiya Arla; Elfrianto Nasution (Journal of Innovation in Research, Education and Culture (JIREC), 2026)
This study is a Research and Development (R&D) study that produces a product in the form of a Smart Box learning media for mathematics learning on solid geometry material in Grade IV at Bakti 1 Private Elementary School. This study aims to determine how the Smart Box media is developed for solid geometry material in Grade IV at Bakti 1 Private Elementary School, to test the validity of the Smart Boxmedia in mathematics learning on solid geometry material in Grade IV at Bakti 1 Private Elementary School, and to test the practicality of the Smart Box media in mathematics learning on solid geometry material in Grade IV at Bakti 1 Private Elementary School. This study uses the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. However, in this study, theresearcher only reached the Implementation stage. The result of this study is a Smart Box media product for mathematics learning on solid geometry material. Based on the validation results, the average score from the media expert was 97.33% (“very valid”), the material expert was 96.36% (“very valid”), and the language expert was 98% (“very valid”). The practicality results based on the teacher’s response reached86% (“very practical”), and the student response trial conducted in Grade IV A at Bakti 1 Private Elementary School with 17 students obtained 95.52% (“very practical”). Based on these results, the Smart Box media developed for mathematics learning on solid geometry material in Grade IV at Bakti 1 Private Elementary School is considered very valid and very practical, meaning that the media is“feasible” to be used in the teaching and learning process.